Interferon induced thrombotic microangiopathy (TMA): Analysis and concise review. (April 2017) - Kundra, Ajay; Wang, Jen Chin
Abstract: Interferon (IFN) has been associated with development of thrombotic microangiopathy including thrombotic thrombocytopenic purpura (TTP) and hemolytic uremic syndrome (HUS). We reviewed literature from the earliest reported association in 1993, to July 2016 and found 68 cases. Analysis of this data shows: (1) Mean age at diagnosis was 47 years (95% CI, 44–50). (2) Majority of cases were seen where IFN was used for the treatment of chronic myelogenous leukemia (CML), multiple sclerosis (MS), chronic hepatitis C virus infection (HCV) and one case each for hairy cell leukemia (HCL) and Sezary syndrome. (3) There were no cases reported for polycythemia vera (PV) or lymphoma. (4) Sex distribution was nearly equivalent with the exception in patients with multiple sclerosis where there was female predominance (12 of 16 with reported data). (5) For pooled analysis, the average duration of treatment with IFN before TMA was diagnosed was 40.4 months. (6) Comparative analysis showed that patients with MS required the highest cumulative dose exposure before developing TMA (MS 68.6 months, CML 35.5 months, HCV 30.4 months). (7) Cases of confirmed TTP (where A disintegrin and Metalloprotease with thrombospondin type 1 motif 13: ADAMTS 13 level was measured) showed presence of an inhibitor. (8) In all cases of confirmed TTP, moderate to severe thrombocytopenia was a striking clinical feature at presentation while this was not a consistent finding in all other cases of TMA. (9) Outcome analysis revealed complete remission in 27 (40%), persistent chronic kidney disease (CKD) in 28 (42%) and fatality in 12 patients (18%). (10) Treatment with corticosteroids, plasma exchange and rituximab resulted in durable responses.